A numerical model of dust particle impacts during a cometary encounter with application to ESA's Comet Interceptor mission. (June 2022) - Haslebacher, Nico; Gerig, Selina-Barbara; Thomas, Nicolas; Marschall, Raphael; Zakharov, Vladimir; Tubiana, Cecilia
Abstract: The attitude perturbations caused by large dust particle impacts on a three-axis stabilized spacecraft during a high velocity encounter with a comet are studied. Specifically, a numerical model is used to make order of magnitude estimations in relation to the European Space Agency's Comet Interceptor mission and help constrain requirements for guidance, navigation and control (GNC). Our model is able to reproduce the measurements acquired by the spin-stabilized Giotto spacecraft during its encounter with comet 1P/Halley in 1986. For realistic scenarios the total change in angular velocity that needs to be corrected can reach 1–10 °/s. At closest approach the median shift of the target object on the Comet Camera (CoCa) detector is typically larger then 10 pixels for the modelled scenarios. Our model shows that the encounter velocity, the spacecraft radius and the attitude control rate are the most critical factors. For the free parameters scaling laws are derived. Highlights: Dust hazards in cometary missions can cause significant attitude perturbations. During a cometary encounter attitude control is necessary to minimize pointing errors caused by dust particle impacts. Our numerical model gives probabilistic results on the number of impacts and the caused attitude perturbations. The model can simulate a wide range of encounter scenarios.